Balancing safety and visibility: Lesbian community building strategies in South Korea. Issue 3 (2nd July 2020) - Jones, Chelle
Abstract: Heteronormative and gender hierarchical organization of economic, legal, and family life intersect to marginalize the lesbian community in South Korea. Lesbian, gay, bisexual, transgender, and queer (LGBTQ) and women's rights movements achieved some gains after democratic transition in the 1990s, but anti-LGBTQ activists target lesbians with harassment and violence. How do lesbians build networks and safe space under these conditions? How do they balance competing needs for visibility and safety? Drawing on 16 months of participant observation and ethnographic interviews, I analyze the relationship between lesbian community growth and safety practices. My intersectional approach examines the heterosexist context in which lesbian social spaces are maintained, and relations of power among LGBTQ, feminist, and anti-LGBTQ groups. Under threat of intersectional violence, lesbian social entrepreneurs withhold information, screen members and rely on spatial tactics to hide in plain sight, prioritizing safety over visibility. Finally, I discuss how some community members marginalized by these safety practices gain access to lesbian spaces.